O cinema de Patricio Guzmán: história e memória entre as imagens políticas e a poética das imagens - Monteiro, Fábio (2022)
This research analyzes the historical interpretations produced by Patricio Guzmán’s cinematography. Born in 1941, Guzmán has developed a transnational career making movies in Chile, Spain, Cuba and Paris. Worldwide awarded since La Batalla de Chile (1975-1979), he is still active developing what he calls as a tetralogy started in 2010 with Nostalgia for the light. The investigation is anchored in the existence of three trilogies, namely: La insurreción de la burguesia (1975), El golpe de Estado (1976) and El poder popular (1979) that make up the “La batalla de Chile”; then Chile, la memoria obstinada (1997), El caso Pinochet (2001) and Salvador Allende (2003) that make up the “trilogy of testimonies” and, finally, Nostalgia de la luz (2010), El botón de nácar (2015) and La cordillera de los sueños (2019) that compose the “trilogy of intimate immensity”. From this assumption, the research understands that these works dialogue with the advances and the limits established by the historiography of contemporary Chile while moving from images valued as direct and destined to poticial denunciation towards a poetics that flirts with the exegesis of images. Besides it, the films promote a self-reflective itinerary that contemplates the monumentalization of its own cinematography